1998
DOI: 10.1097/00000539-199803000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Loading Modifications Induced by Pneumoperitoneum

Abstract: Insufflation of gas into the abdominal cavity results in hemodynamic changes during laparoscopic procedures. We found that echocardiographic and blood pressure effects associated with gas insufflation were transient, indicating mediation by factors besides intraabdominal pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
8

Year Published

2000
2000
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 26 publications
1
12
0
8
Order By: Relevance
“…While most studies 9,1518 including the current one found an increase in MAP, one study reported a decrease of 17%. 3 Changes in HR have been variably reported, with increased HR, 15 no change in HR, 9 and decreased HR.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…While most studies 9,1518 including the current one found an increase in MAP, one study reported a decrease of 17%. 3 Changes in HR have been variably reported, with increased HR, 15 no change in HR, 9 and decreased HR.…”
Section: Discussionmentioning
confidence: 50%
“…Several authors 3,9,1518 have reported on physiological effects of pneumoperitoneum in the Trendelenburg position. These reports differ from the current one in that the hemodynamic observations were made by comparing patients with their baseline anesthetized state before and after placement in the Trendelenburg position.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular changes have been characterized by many clinical studies [3, 4, 5, 6, 7, 8, 27]. Most of these studies reported increased systemic and pulmonary vascular resistance and reduction of cardiac index when laparoscopy was performed at about 15 mm Hg and head up tilt 10°.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…Three minutes after the onset of pneumoperitoneum at the pressure of 8–12 mm Hg, Branche et al [7]observed a 25.7% increase in mean arterial pressure, a 49% increase in left ventricular end-systolic wall stress (a measure of left ventricular afterload ) and a 17% decrease in fractional area shortening (a measure of left ventricular function-contractility). All measured variables returned to preinsufflation values after 30 min of pneumoperitoneum and thereafter were no longer significantly affected by postural changes (10° head-up position) or pneumoperitoneum exsufflation.…”
Section: Cardiovascular Systemmentioning
confidence: 99%
“…The effects of both Trendelenburg's position and pneumoperitoneum on intrathoracic volumes, compliance of lungs and circulation are complex and have not been widely investigated, in contrast to pneumoperitoneum and head up tilt for laparoscopic cholecystectomy (17)(18)(19). Harris et al examined cardiovascular alterations during laparoscopic colectomy with pneumoperitoneum and head-down tilt.…”
Section: Effect Of Pneumoperitoneum and Head-down Tiltmentioning
confidence: 99%